The 7th Census of Italian agriculture: Characteristics, structures and dynamics of generational renewal - Francesco Licciardo; Serena Tarangioli; Giuseppe Gargano; Stefano Tomassini; Barbara Zanetti (Italian Review of Agricultural Economics (REA), 2023)
The 7th General Census of Italian Agriculture offers an opportunity to assess the current state and key trends within Italian agriculture. One pressing issue that it highlights is the aging workforce in this sector. Encouraging youth entrepreneurship is a primary goal endorsed by both national and European policies. It aims to ensure a seamless generational transition while promoting a more innovative and dynamic agricultural sector. Agriculture faces a set of critical challenges in the years ahead, including efficiency enhancement, resilience building, digitalization, and sustainability practices. These necessitate the integration of fresh, well-qualified entrepreneurial talent, making generational turnover not only highly desirable but also essential. This article employs data from the latest Census to delve into the age distribution of farm managers, placing a particular emphasis on the younger demographic and the farms they oversee. The study aims to scrutinize the primary shifts in the demographic makeup of agricultural holdings, with a specific focus on contrasting young and elderly farmers. The outcomes of this analysis bring to the forefront an intriguing generational shift marked by well-educated agricultural entrepreneurs who exhibit a proclivity for innovation and the adoption of digital technologies. This cohort of farmers is actively diversifying their agricultural pursuits, with a strong commitment to environmental sustainability and the market. Nonetheless, despite these commendable efforts, they continue to grapple with establishing a firm position in the sector.
Keywords: Q10; Q12; 330; ageing farmers; agricultural Census data; Common Agricultural Policy; farm structures; generational renewal; young farmers